Manganese zinc ferrite material as well as preparation method and application thereof

By performing multiple steps in preparation and treatment of the raw materials of manganese-zeb ferrite materials, including ball milling, pre-firing, molten salt reaction and salt washing treatment, and adding specific auxiliary additives, the problems of insufficient energy storage performance and high magnetic loss of composite magnetic materials in the prior art are solved, and materials with high energy storage and low magnetic loss are prepared.

CN119683988APending Publication Date: 2025-03-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311237849.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

It is difficult to develop composite magnetic materials with high energy storage and low magnetic loss in the prior art, especially in improving the energy storage performance of magnetic materials and reducing magnetic losses.

Method used

A method of preparing a manganese zinc ferrite material is adopted, including first ball milling, pre-firing, second ball milling, molten salt reaction and salt washing treatment on the raw material, and through these steps, a composite material with high energy storage and low magnetic loss is obtained. This method optimizes ball milling and sintering conditions by adding auxiliary additives such as CaCO3, SiO2, ZrO2, Co2O3 and TiO2, improves the permeability and resistivity of the material, and reduces eddy current loss.

Benefits of technology

The prepared manganese zinc ferrite material has the advantages of high energy storage and low power consumption, and exhibits a higher complex magnetic permeability real part (μ’) and a lower complex magnetic permeability imaginary part (μ’) at different frequencies, specifically manifested as μ’>30, μ’<1.5.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004466174750000141
    Figure BDA0004466174750000141
  • Figure BDA0004466174750000151
    Figure BDA0004466174750000151
Patent Text Reader

Abstract

The invention provides a manganese zinc ferrite material as well as a preparation method and application thereof. The preparation method comprises the following steps: sequentially carrying out first ball milling, pre-sintering, second ball milling, molten salt reaction and salt leaching treatment on raw materials of the manganese-zinc ferrite material to obtain the manganese-zinc ferrite material. The manganese zinc ferrite material prepared by the invention has the beneficial effects of high energy storage and low energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic powder core materials and relates to a manganese-zinc ferrite material, in particular to a manganese-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern electronic technology industry, miniaturization, high frequency and low power consumption of electronic devices have become an inevitable trend of development. Magnetic powder cores have the advantages of high saturation magnetic induction intensity, low loss, low noise and low cost. They have been widely used in high-frequency power filters, uninterruptible power supply power correctors, power chokes, pulse transformers, etc. Improving the magnetic permeability of magnetic powder core materials and reducing losses are also major difficulties currently faced.

[0003] There are many related studies on composite magnetic powder core materials disclosed in the prior art, but the research on composite magnetic materials is rarely mentioned.

[0004] CN114654823B discloses a Mn-Zn ferrite-FeSiAl composite absorbing material and a preparation method thereof. By means of a layered alternating stacking and hot pressing method, high impedance matching is effectively achieved, and the high performance requirements of large bandwidth and strong absorption can be met. However, it does not disclose how to increase the energy storage of magnetic materials and reduce the magnetic loss of magnetic materials.

[0005] CN113658768A discloses a FeSiAl / MnZn ferrite soft magnetic composite powder core with stable magnetic permeability and low loss and a preparation method thereof, wherein the preparation method mainly adopts a phosphoric acid / MnZn ferrite composite coating process, and the phosphated FeSiAl powder is coated with MnZn ferrite by a high-energy ball milling method. However, it does not disclose how to improve the energy storage performance of magnetic materials.

[0006] Therefore, how to develop a composite material with high energy storage and low magnetic loss is an important research direction in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a manganese-zinc ferrite material and a preparation method and application thereof, so as to prepare a composite material with high energy storage and low magnetic loss.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] One of the purposes of the present invention is to provide a method for preparing a manganese-zinc ferrite material, the preparation method comprising:

[0010] The raw materials of the manganese-zinc ferrite material are subjected to first ball milling, pre-sintering, second ball milling, molten salt reaction and salt washing treatment in sequence to obtain the manganese-zinc ferrite material.

[0011] The present invention performs the first ball milling on the raw materials of manganese zinc ferrite so that the raw materials are fully mixed, thereby promoting the reaction between the mixed materials; pre-firing can decompose a part of the oxides in the raw materials, eliminate impurities that are easily volatile, obtain a uniform mixture, promote the initial solid phase reaction of the first ball milled materials, generate pre-firing shrinkage, and reduce the shrinkage rate of the product; auxiliary additives can be added in the second ball milling, the pre-firing materials and the auxiliary additives after pre-firing are mixed, and the pre-firing materials are ball milled into particles of a certain size after the second ball milling, which is beneficial to subsequent molding and performance improvement; in the molten salt reaction, the salt is in a molten state during the sintering process, which provides a reaction environment similar to a liquid phase reaction for the reaction, helps the contact and reaction of the raw materials, reduces the sintering temperature, avoids agglomeration, obtains the expected microstructure, affects the degree of solid phase reaction and the phase composition of the material, and thus improves the activity and dispersibility of the manganese zinc ferrite.

[0012] As a preferred technical solution of the present invention, the raw materials of the manganese-zinc ferrite material include a zinc source, an iron source and a manganese source.

[0013] Preferably, the zinc source comprises ZnO.

[0014] Preferably, the iron source comprises Fe 2 O 3 .

[0015] Preferably, the manganese source comprises Mn 2 O 3 .

[0016] Preferably, the total amount of the first ball milling material is 100%, and the raw materials of the manganese-zinc ferrite material include 2.5-3% ZnO, 71-72% Fe 2 O 3 and 25~26.5%Mn 2 O 3 , wherein the mass fraction of ZnO is 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%, etc., and the Fe 2 O 3 The mass fraction of Mn is 71%, 71.1%, 71.2%, 71.3%, 71.4%, 71.5%, 71.6%, 71.7%, 71.8%, 71.9% or 72%, etc. 2 O 3 The mass fraction is 25%, 25.2%, 25.4%, 25.6%, 25.8%, 26%, 26.1%, 26.2%, 26.3%, 26.4% or 26.5%, etc., but is not limited to the listed values, and other unlisted values ​​within the above-mentioned numerical ranges are also applicable.

[0017] As a preferred technical solution of the present invention, the first ball milling includes wet ball milling.

[0018] Preferably, the ball milling media of the first ball milling comprises zirconia balls.

[0019] Preferably, the first ball milling time is 1 to 2 hours, wherein the time can be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the first ball milling product is dried after the first ball milling.

[0021] As a preferred technical solution of the present invention, the pre-calcination heating rate is 2 to 3°C / min, wherein the heating rate can be 2°C / min, 2.1°C / min, 2.2°C / min, 2.3°C / min, 2.4°C / min, 2.5°C / min, 2.6°C / min, 2.7°C / min, 2.8°C / min, 2.9°C / min or 3°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] The setting of the pre-firing heating rate in the present invention is used to adjust whether the lattice structure can be corrected in time, change the activity of the pre-firing material, etc.

[0023] Preferably, the pre-firing temperature is 850-950°C, wherein the temperature may be 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] The pre-firing temperature in the present invention will affect the activity, density, magnetic permeability, loss, shrinkage, etc. of the ferrite. Ferrites with different properties require different pre-firing temperatures to ensure their better comprehensive properties.

[0025] Preferably, the pre-burning time is 1 to 3 hours, wherein the time may be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] As a preferred technical solution of the present invention, auxiliary additives are added during the second ball milling.

[0027] Preferably, the auxiliary additive includes CaCO 3 、SiO 2 、ZrO 2 、Co 2 O3 and TiO 2 .

[0028] In the present invention, Ca 2+ The radius is larger than the tetrahedron and octahedron gaps in the face-centered cubic spinel phase and cannot enter the lattice, so it is mainly enriched at the ferrite grain boundary, increasing the grain boundary resistivity of the material and reducing the eddy current loss of the ferrite. However, due to CaCO 3 It will also hinder the displacement of the grain boundary domain wall, which will lead to a decrease in the magnetic permeability of the manganese-zinc material. 2 , which exists at the grain boundaries, increases the resistivity of the material, and also reacts with Fe 2 O 3 Formation of low melting point FeSiO 4 , forming a liquid phase during the sintering process, promoting uniform grain growth, better grain uniformity, and improving the magnetic permeability of the material. 3 With SiO 2 , so that during high temperature sintering, CaSiO 3 Another phase precipitates at the grain boundary, which makes the grain boundary thicker, greatly increases the grain boundary resistivity, and reduces eddy current loss. The effect is better than CaCO 3 and SiO 2 Added alone for a substantial boost.

[0029] The present invention adds ZrO 2 The magnetic permeability of ferrite increases first and then decreases, and when the magnetic permeability is high, the loss is also minimized.

[0030] The present invention adds a small amount of Co 2 O 3 Generating CoFe 2 O 4 , and CoFe 2 O 4 The magnetocrystalline anisotropy constant K 1 is positive, MnZn ferrite K 1 is negative, which is K 1 →0, and the magnetostriction coefficient λ s →0, according to μi∝M s ^2 / (K 1 +λ s *σ) shows that adding Co 2 O 3 Improve the magnetic permeability of the material.

[0031] The present invention adds TiO 2 , Ti 4+ When entering the spinel lattice, Fe 3+ Transformed into Fe 2+ , Ti 4+ , Fe 2+ The combination can make K→0, so that the magnetization is mainly reversible domain transfer, reducing hysteresis loss.

[0032] Preferably, based on the total amount of the ball milled material in the first ball milling, the CaCO 3 The addition amount is 500-700ppm, wherein the addition amount can be 500ppm, 520ppm, 540ppm, 560ppm, 580ppm, 600ppm, 620ppm, 640ppm, 660ppm, 680ppm or 700ppm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, based on the total amount of the ball milled material in the first ball milling, the SiO 2 The amount of solution added is 250 to 350 ppm, wherein the amount added can be 250 ppm, 260 ppm, 270 ppm, 280 ppm, 290 ppm, 300 ppm, 310 ppm, 320 ppm, 330 ppm, 340 ppm or 350 ppm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, CaSO 3 、SiO 2 Too much or too little addition will cause the manganese-zinc ferrite material to reduce μ' and increase μ".

[0035] Preferably, based on the total amount of the first ball milling material, the ZrO 2 The addition amount is 200-300ppm, wherein the addition amount can be 200ppm, 210ppm, 220ppm, 230ppm, 240ppm, 250ppm, 260ppm, 270ppm, 280ppm, 290ppm or 300ppm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, based on the total amount of the first ball milling material, the Co 2 O 3The addition amount is 1750-2250ppm, wherein the addition amount can be 1750ppm, 1780ppm, 1800ppm, 1820ppm, 1840ppm, 1860ppm, 1880ppm, 1900ppm, 1920ppm, 1950ppm, 2000ppm, 2050ppm, 2100ppm, 2150ppm, 2200ppm or 2250ppm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the TiO 2 The amount of solution added is 150 to 350 ppm, wherein the amount added can be 150 ppm, 200 ppm, 250 ppm, 300 ppm or 350 ppm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the second ball milling comprises wet ball milling.

[0039] Preferably, the second ball milling time is 2 to 4 hours, wherein the time can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the product after the second ball milling is dried.

[0041] As a preferred technical solution of the present invention, the molten salt reaction includes: adding salt to the product after the second ball milling, and sequentially performing dry mixing and sintering to complete the molten salt reaction.

[0042] Preferably, the salt comprises K 2 SO 4 , KCl, KNO 3 Or Na 2 SO 4 Any one or a combination of at least two of the above, wherein a typical but non-limiting example of the combination is: K 2 SO 4 Combination of KCl and KCl and KNO 3 Combination of KNO 3 and Na 2 SO 4 combinations of etc.

[0043] Preferably, the mass fraction of the salt in the product after the second ball milling is 20-50%, wherein the mass fraction can be 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] As a preferred technical solution of the present invention, the sintering atmosphere includes oxygen and inert gas.

[0045] Preferably, based on the total volume of the oxygen and the inert gas as 100%, the volume fraction of the oxygen is 1 to 1.5%, wherein the volume fraction may be 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the inert atmosphere comprises nitrogen and / or argon.

[0047] Preferably, the sintering heating rate is 2 to 3°C / min, wherein the heating rate may be 2°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min or 3°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the sintering temperature is 1100-1200°C, wherein the temperature may be 1100°C, 1120°C, 1140°C, 1160°C, 1180°C or 1200°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] When the sintering temperature in the present invention is too low, some grains have not grown yet, the uniformity is poor, large gaps are generated between the grains, and the solid phase reaction is not complete; when the sintering temperature is too high, some grains grow secondary, and a large number of pores are generated inside the grains and at the grain boundaries, increasing the porosity and making ZnFeO 4 Produces Fe 3 O 4 And ZnO, but ZnO will decompose at high temperature, causing Zn to volatilize and affect the performance of ferrite.

[0050] Preferably, the sintering time is 2 to 4 hours, wherein the time may be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the salt washing solution is deionized water.

[0052] Preferably, the temperature of the salt washing treatment is 70-90°C, wherein the temperature may be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] As a preferred technical solution of the present invention, the preparation method comprises:

[0054] The raw material of the manganese-zinc ferrite material is subjected to a first ball milling, a pre-sintering, a second ball milling, a molten salt reaction and a salt washing treatment in sequence to obtain the manganese-zinc ferrite material;

[0055] The first ball milling time is 1 to 2 hours;

[0056] The heating rate of pre-sintering is 2-3°C / min, the temperature is 850-950°C and the time is 1-3h;

[0057] The second ball milling time is 2 to 4 hours;

[0058] The molten salt reaction includes: adding salt to the product after the second ball milling, and performing dry mixing and sintering in sequence to complete the molten salt reaction, the sintering heating rate is 2-3°C / min, the temperature is 1100-1200°C and the time is 2-4h.

[0059] The second object of the present invention is to provide a manganese-zinc ferrite material, wherein the manganese-zinc ferrite material is prepared by the preparation method of the manganese-zinc ferrite material described in one of the objects.

[0060] The third object of the present invention is to provide an application of the manganese-zinc ferrite material as described in the second object, wherein the manganese-zinc ferrite material is applied in the field of magnetic powder core materials.

[0061] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The manganese-zinc ferrite material prepared by the invention has the advantages of high energy storage and low power consumption. At 10 MHz, 20 MHz, 50 MHz and 100 MHz, the material has higher μ' and lower μ", μ'>30, μ"<1.5. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0065] Example 1

[0066] This embodiment provides a method for preparing a manganese-zinc ferrite material, the preparation method comprising:

[0067] The raw materials of the manganese-zinc ferrite material are subjected to first ball milling, pre-sintering, second ball milling, salt-adding and mixing, sintering and salt-washing treatment in sequence to obtain the manganese-zinc ferrite material.

[0068] Wherein, based on the mass of the manganese-zinc ferrite material as 100%, the raw materials of the manganese-zinc ferrite material are 2.8% ZnO, 71.4% Fe 2 O 3 and 25.8% Mn 2 O 3 ;

[0069] First ball milling: the raw materials are mixed by wet ball milling, the ball milling medium is zirconia ball, the ball milling time is 1.5h, and the raw materials are dried after ball milling;

[0070] Pre-burning: put the product after the first ball milling into the furnace, the heating rate is 2℃ / min, the pre-burning temperature is 900℃, and the pre-burning time is 2h;

[0071] Secondary ball milling: Add additives to the ball mill for wet sand milling. The secondary ball milling time is 3 hours, and the secondary ball milling is followed by drying. The additives include CaCO 3 、SiO 2 、ZrO 2 、Co 2 O 3 and TiO 2 , CaCO 3 The addition amount is 600ppm, SiO 2 The addition amount is 300ppm, ZrO 2 The addition amount is 250ppm, Co 2 O 3 The addition amount is 2000ppm, TiO 2 The addition amount is 200ppm;

[0072] Molten salt reaction: Add analytical pure K to the product after secondary ball milling 2 SO 4 Dry mixing was performed, and the salt-added mixed product was sintered in an atmosphere with an oxygen content of 1.25% and the rest being nitrogen, with a sintering heating rate of 2.5°C / min, a sintering temperature of 1150°C, and a sintering time of 3h;

[0073] Salt washing treatment: wash the sintered product with salt, add the sintered material into the washing solution and deionized water, and heat the deionized water to 80°C and stir with a glass rod, then pour out the washing solution, repeat more than 3 times until there is no K in the fluorescence scan.

[0074] Example 2

[0075] This embodiment provides a method for preparing a manganese-zinc ferrite material, the preparation method comprising:

[0076] The raw materials of the manganese-zinc ferrite material are subjected to first ball milling, pre-sintering, second ball milling, salt-adding and mixing, sintering and salt-washing treatment in sequence to obtain the manganese-zinc ferrite material.

[0077] Wherein, based on the mass of the manganese-zinc ferrite material as 100%, the raw materials of the manganese-zinc ferrite material are 3% ZnO, 72% Fe 2 O 3 and 25.5% Mn 2 O 3 ;

[0078] First ball milling: the raw materials are mixed by wet ball milling, the ball milling medium is zirconium oxide ball, the ball milling time is 1 hour, and the ball milling is dried after drying;

[0079] Pre-burning: put the product after the first ball milling into the furnace, the heating rate is 2.5℃ / min, the pre-burning temperature is 880℃, and the pre-burning time is 1h;

[0080] Secondary ball milling: Add additives to the ball mill for wet sand milling. The secondary ball milling time is 2 hours, and the secondary ball milling is followed by drying. The additives include CaCO 3 、SiO 2 、ZrO 2 、Co 2 O 3 and TiO 2 , CaCO 3 The addition amount is 500ppm, SiO 2 The addition amount is 250ppm, ZrO 2 The addition amount is 200ppm, Co 2 O 3 The addition amount is 1750ppm, TiO 2 The addition amount is 150ppm;

[0081] Molten salt reaction: Add analytical pure KNO to the product after secondary ball milling 3 Dry mixing was performed, and the salt-added mixed product was sintered in an atmosphere with an oxygen content of 1% and the rest being nitrogen, with a sintering heating rate of 2°C / min, a sintering temperature of 1100°C, and a sintering time of 4h;

[0082] Salt washing treatment: wash the sintered product with salt, add the sintered material into the washing solution deionized water, and heat the deionized water to 70°C, stir with a glass rod, then pour out the washing solution, repeat more than 3 times until there is no K in the fluorescence scan.

[0083] Example 3

[0084] This embodiment provides a method for preparing a manganese-zinc ferrite material, the preparation method comprising:

[0085] The raw materials of the manganese-zinc ferrite material are subjected to first ball milling, pre-sintering, second ball milling, salt-adding and mixing, sintering and salt-washing treatment in sequence to obtain the manganese-zinc ferrite material.

[0086] Wherein, based on the mass of the manganese-zinc ferrite material as 100%, the raw materials of the manganese-zinc ferrite material are 2.5% ZnO, 71% Fe 2 O 3 and 26.5% Mn 2 O 3 ;

[0087] First ball milling: the raw materials are mixed by wet ball milling, the ball milling medium is zirconia ball, the ball milling time is 2h, and the ball milling is dried after the ball milling;

[0088] Pre-burning: put the product after the first ball milling into the furnace, the heating rate is 3℃ / min, the pre-burning temperature is 850℃, and the pre-burning time is 3h;

[0089] Secondary ball milling: Add additives to the ball mill for wet sand milling. The secondary ball milling time is 3 hours, and the secondary ball milling is followed by drying. The additives include CaCO 3 、SiO 2 、ZrO 2 、Co 2 O 3 and TiO 2 , CaCO 3 The addition amount is 700ppm, SiO 2 The addition amount is 350ppm, ZrO 2 The addition amount is 300ppm, Co 2 O 3 The addition amount is 2250ppm, TiO 2 The addition amount is 350ppm;

[0090] Molten salt reaction: add analytical pure KCl to the product after secondary ball milling for dry mixing, and sinter the product in an atmosphere with an oxygen content of 1.5% and nitrogen as the rest. The heating rate of sintering is 3°C / min, the sintering temperature is 1200°C, and the sintering time is 2h.

[0091] Salt washing treatment: wash the sintered product with salt, add the sintered material into the washing solution deionized water, and heat the deionized water to 90°C, stir with a glass rod, then pour out the washing solution, repeat more than 3 times until there is no K in the fluorescence scan.

[0092] Example 4

[0093] In this embodiment, in addition to 2 O 3 Except for adjusting to 1500 ppm, other conditions are the same as those in Example 1.

[0094] Example 5

[0095] In this embodiment, in addition to 2 O 3 Except for adjusting to 1750 ppm, other conditions are the same as those in Example 1.

[0096] Example 6

[0097] In this embodiment, in addition to 2 O 3 Except for adjusting to 2250 ppm, other conditions are the same as those in Example 1.

[0098] Example 7

[0099] In this embodiment, in addition to 2 O 3 Except for adjusting to 2500 ppm, other conditions are the same as those in Example 1.

[0100] Example 8

[0101] In this embodiment, in addition to CaCO 3 Adjusted to 400ppm, SiO 2 Except for adjusting to 200 ppm, other conditions are the same as those in Example 1.

[0102] Example 9

[0103] In this embodiment, in addition to CaCO 3 Adjusted to 500ppm, SiO 2 Except for adjusting to 250 ppm, other conditions are the same as those in Example 1.

[0104] Example 10

[0105] In this embodiment, in addition to CaCO3 Adjusted to 700ppm, SiO 2 Except for adjusting to 350 ppm, other conditions are the same as those in Example 1.

[0106] Embodiment 11

[0107] In this embodiment, in addition to CaCO 3 Adjusted to 800ppm, SiO 2 Except for adjusting to 400 ppm, other conditions are the same as those in Example 1.

[0108] Example 12

[0109] In this embodiment, no CaCO is added in the second ball mill. 3 and SiO 2 Except for this, other conditions are the same as those in Example 1.

[0110] Embodiment 13

[0111] In this embodiment, ZrO is not added in the second ball mill. 2 Except for this, other conditions are the same as those in Example 1.

[0112] Embodiment 14

[0113] In this embodiment, Co is not added in the second ball mill. 2 O 3 Except for this, other conditions are the same as those in Example 1.

[0114] Embodiment 15

[0115] In this embodiment, no TiO is added in the second ball mill. 2 Except for this, other conditions are the same as those in Example 1.

[0116] Example 16

[0117] In this embodiment, analytical pure K 2 SO 4 Replaced with analytical grade Na 2 SO 4 Except for this, other conditions are the same as those in Example 1.

[0118] Embodiment 17

[0119] In this embodiment, analytical pure K 2 SO 4 Except for replacing with analytical grade KCl, other conditions were the same as those in Example 1.

[0120] Embodiment 18

[0121] Except that the sintering temperature is replaced with 1050° C., other conditions of this embodiment are the same as those of embodiment 1.

[0122] Embodiment 19

[0123] Except that the sintering temperature is changed to 1100° C., other conditions of this embodiment are the same as those of embodiment 1.

[0124] Embodiment 20

[0125] Except that the sintering temperature is changed to 1200° C., other conditions of this embodiment are the same as those of embodiment 1.

[0126] Embodiment 21

[0127] Except that the sintering temperature is changed to 1250° C., other conditions in this embodiment are the same as those in Embodiment 1.

[0128] Embodiment 22

[0129] In this embodiment, except that the oxygen content in the sintering atmosphere is replaced with 0.75%, other conditions are the same as those in embodiment 1.

[0130] Embodiment 23

[0131] In this embodiment, except that the oxygen content in the sintering atmosphere is replaced with 1%, other conditions are the same as those in Embodiment 1.

[0132] Embodiment 24

[0133] In this embodiment, except that the oxygen content in the sintering atmosphere is replaced with 1.5%, other conditions are the same as those in embodiment 1.

[0134] Embodiment 25

[0135] In this embodiment, except that the oxygen content in the sintering atmosphere is replaced with 1.75%, other conditions are the same as those in embodiment 1.

[0136] Comparative Example 1

[0137] Except that the first ball milling was not performed, other conditions in this comparative example were the same as those in Example 1.

[0138] Comparative Example 2

[0139] Except that pre-firing was not performed, other conditions in this comparative example were the same as those in Example 1.

[0140] Comparative Example 3

[0141] In this comparative example, except that the salt adding and mixing method is replaced by the solid phase method, the solid phase method removes the salt adding and washing stages, and the sintering temperature is increased by 100°C, other conditions are the same as those in Example 1.

[0142] The energy storage and magnetic loss tests were performed on the manganese-zinc ferrite materials prepared in Examples 1-25 and Comparative Examples 1-3. The test results are shown in Table 1.

[0143] Among them, the magnetic permeability μi=μ'-μ"i, μ' is the real part of the complex magnetic permeability, which represents the energy storage of the magnetic material, and μ" is the imaginary part of the complex magnetic permeability, which represents the magnetic loss of the material.

[0144] Table 1

[0145]

[0146]

[0147] The manganese-zinc ferrite materials in Examples 1-3 of the present invention have the properties of high energy storage and low magnetic loss.

[0148] By comparing Example 1 with Examples 4-7, it can be seen that the addition of Co 2 O 3 , generating CoFe 2 O 4 , and CoFe 2 O 4 The magnetocrystalline anisotropy constant K 1 is positive, while MnZn ferrite K 1 From negative, it is K 1 →0, and the magnetostriction coefficient λ s →0, according to μi∝M s ^2 / (K 1 +λ s *σ), which can improve the magnetic permeability of the material. 2 O 3 The expected effect can only be achieved if the addition amount is kept within a certain range. When the addition amount exceeds the range, the improvement effect of the performance of manganese-zinc ferrite is not obvious.

[0149] By comparing Example 1 with Examples 8-11, it can be seen that CaCO 3 and SiO 2 If the amount exceeds the preferred addition range, the performance of the manganese-zinc ferrite decreases.

[0150] By comparing Example 1 with Examples 12-15, it can be seen that no CaCO3, SiO2, ZrO, Co, etc. are added to the MnZn ferrite. 2 O 3 、TiO 2 One or both of these will degrade its performance.

[0151] By comparing Example 1 with Examples 16-17, it can be seen that the analytically pure K 2 SO4 Replace with analytical grade Na 2 SO 4 , KCl, has basically no effect on its performance, so they can both be used.

[0152] By comparing Example 1 with Examples 18-21, it can be seen that when the sintering temperature is too low, K 2 SO 4 It has not yet entered the molten state, the reaction is not complete, the grain size is very different, the uniformity is poor, the pores are scattered at the grain boundaries and inside the grains, the porosity is high, and the magnetic permeability, residual magnetic induction intensity and other properties are poor; when the sintering temperature is too high, the grains grow abnormally, and as Fe 2 O 3 Due to the reduction of and volatilization of Zn, the pores grow rapidly, the grain boundaries deform, and the density, magnetic permeability and residual magnetic induction intensity decrease significantly.

[0153] By comparing Example 1 with Examples 22-25, it can be seen that when the oxygen content is kept within a certain range, a complete MnFe 2 O 4 and ZnFe 2 O 4 When the oxygen content is too high, Mn and Fe ions will appear at high prices, producing Mn 3 O 4 , Fe 2 O 3 When the oxygen content is too low, Mn and Fe ions will appear at low prices to produce MnO and FeO, both of which will precipitate into other phases, which will have a significant deterioration effect on the magnetic properties of the material.

[0154] It can be seen from Example 1 and Comparative Examples 1-3 that the first ball milling is not performed, and the function of the first ball milling is mainly to mix the raw materials, refine the raw materials, improve the uniformity of the components, and increase the activity of the raw materials. Without pre-burning, the raw materials will not undergo a preliminary solid-phase reaction and the optimal performance of the ferrite cannot be guaranteed. Not adding salt is equivalent to the solid-phase method, and the performance is reduced.

[0155] By comparing Example 1 with Comparative Example 3, it can be seen that the performance of the manganese-zinc ferrite material prepared by the molten salt method is better than that by the solid phase method and the molten salt method (adding salt and mixing before sintering). The main reason is that the material prepared by the solid phase method will agglomerate, while the K 2 SO 4 It is in a molten state during the sintering process, providing a reaction environment similar to a liquid phase reaction, which is conducive to the contact and reaction of the raw materials, reduces the sintering temperature, and avoids agglomeration.

[0156] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a manganese-zinc ferrite material, characterized in that: The preparation method comprises: The raw materials of the manganese-zinc ferrite material are subjected to first ball milling, pre-sintering, second ball milling, molten salt reaction and salt washing treatment in sequence to obtain the manganese-zinc ferrite material.

2. The preparation method according to claim 1, characterized in that: The raw materials of the manganese-zinc ferrite material include a zinc source, an iron source and a manganese source; Preferably, the zinc source comprises ZnO; Preferably, the iron source comprises Fe2O3; Preferably, the manganese source comprises Mn2O3; Preferably, taking the total amount of the first ball milling material as 100%, the raw materials of the manganese-zinc ferrite material include 2.5-3% ZnO, 71-72% Fe2O3 and 25-26.5% Mn2O3 in terms of mass fraction.

3. The preparation method according to claim 1 or 2, characterized in that: The first ball milling includes wet ball milling; Preferably, the ball milling media of the first ball milling comprises zirconium oxide balls; Preferably, the first ball milling time is 1 to 2 hours; Preferably, the first ball milling product is dried after the first ball milling.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The heating rate of the pre-burning is 2-3°C / min; Preferably, the pre-burning temperature is 850-950°C; Preferably, the pre-burning time is 1 to 3 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Adding auxiliary additives in the second ball milling; Preferably, the auxiliary additives include CaCO3, SiO2, ZrO2, Co2O3 and TiO2; Preferably, based on the total amount of the ball mill material in the first ball mill, the amount of CaCO3 added is 500-700 ppm; Preferably, based on the total amount of the ball mill material in the first ball milling, the amount of SiO2 added is 250-350 ppm; Preferably, based on the total amount of the first ball milling material, the amount of ZrO2 added is 200-300 ppm; Preferably, based on the total amount of the first ball milling material, the amount of Co2O3 added is 1750-2250ppm; Preferably, based on the total amount of the first ball milling material, the amount of TiO2 added is 150 to 350 ppm; Preferably, the second ball milling comprises wet ball milling; Preferably, the second ball milling time is 2 to 4 hours; Preferably, the product after the second ball milling is dried.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The molten salt reaction comprises: adding salt to the product after the second ball milling, and sequentially performing dry mixing and sintering to complete the molten salt reaction; Preferably, the salt comprises any one or a combination of at least two of K2SO4, KCl, KNO3 or Na2SO4; Preferably, the mass fraction of the salt in the product after the second ball milling is 20-50%.

7. The preparation method according to claim 6, characterized in that: The sintering atmosphere includes oxygen and inert gas; Preferably, based on the total volume of the oxygen and the inert gas being 100%, the volume fraction of the oxygen is 1 to 1.5%; Preferably, the inert gas comprises nitrogen and / or argon; Preferably, the heating rate of the sintering is 2-3°C / min; Preferably, the sintering temperature is 1100-1200°C; Preferably, the sintering time is 2 to 4 hours; Preferably, the salt washing solution used in the salt washing step is deionized water; Preferably, the temperature of the salt washing treatment is 70-90°C.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The raw material of the manganese-zinc ferrite material is subjected to a first ball milling, a pre-sintering, a second ball milling, a molten salt reaction and a salt washing treatment in sequence to obtain the manganese-zinc ferrite material; The first ball milling time is 1 to 2 hours; The heating rate of pre-sintering is 2-3°C / min, the temperature is 850-950°C and the time is 1-3h; The second ball milling time is 2 to 4 hours; Salt is added to the product after the second ball milling, and dry mixing and sintering are performed in sequence to complete the molten salt reaction. The sintering heating rate is 2-3°C / min, the temperature is 1100-1200°C, and the time is 2-4h.

9. A manganese-zinc ferrite material, characterized in that: The manganese-zinc ferrite material is prepared by the method for preparing the manganese-zinc ferrite material according to any one of claims 1 to 8.

10. An application of the manganese-zinc ferrite material as claimed in claim 9, characterized in that: The manganese-zinc ferrite material is applied in the field of magnetic powder core materials.

Citation Information

Cited By

  • Ferrite material as well as preparation method and application thereof

    CN120247545A